The Study on Determinants of Entrepreneurial Investment: A Case Study in Phitsanulok - ฤกษ์วรารักษ์ วราวุธ; วัฒนดำรงค์ ภคพร; พูลเจริญ ณัฐเชษฐ์ (Community and Social Development Journal, 2018)
Study on investment factors of entrepreneurs in Phitsanulok province. This article only shows the results of qualitative studies using in-depth interviews with 30 entrepreneurs Phitsanulok in 7 business sectors. The study found that the main factors contributing to the investment decision in Phitsanulok were: the location; the trend of provincial economic growth; direct experience of entrepreneurs who have invested in the area; policy of central headquarters; and volume of border trade. Data sources for investment planning or further expansion in Phitsanulok were: the experience of incumbent entrepreneurs already in the area and insider information from industry practitioners. But for medium-sized businesses, data from R&D was relied heavily upon before making a new investment decision, as well as data from financial advisors of the business. The satisfaction level with the services that entrepreneurs experienced on investment in Phitsanulok province, regarding travel, food, accommodation, facilities and basic infrastructure is averagely acceptable. Only some amendments are needed, including improvement of infrastructure and services in some areas, especially about traffic jams during rush hours as well as the sub-standard government services in various activities. Business investors in general agree that even though Phitsanulok has prospect as the center of the region, the province is not quite ready in many ways. The government should promote the allocation of budget for infrastructure development in the province as well as for laborers’ continuous skill development. The ASEAN Economic Community does not negatively impact the investment climate. It should rather leads to product and service improvement.